DIGNITY OF LIFE: BUDDHIST AND CATHOLIC MORAL REASONING - Lertjitlekha, Cherdchai; Daodee, Supaporn (Asian Horizons, 2015)
The purpose of this study is to explore a common ground for Buddhist and Catholic ethics in one specific area of bioethics, namely ‘dignity of life,‘ by focusing on the duty of conserving life at the terminal stage. The study builds upon documentary research which examined religious texts regarding the doctrines and ethics in both Theravada Buddhism and Catholic and the attempts to see the common ground and their particularities of augmentations of the dignity of life. It creates an ethical dialogue which involves Theravada Buddhist ethics and Catholic ethics in an interreligious context for the betterment. Its result will provide the information that may support the healthcare personnel to give proper services to Buddhist or Catholic dying patients.